Characterization of sludge from industries for possible recovery in arts - Rodríguez Mora, Karina (2023)
Sludge from oxidation ponds from different industries was evaluated to study its composition through a chemical characterization and determine a possible route for its recovery. For the characterization of the sludge, gravimetry for SiO2 content, infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, X-ray energy dispersion spectrometry (EDS), and X-ray fluorescence (XRF) were used. It was determined that the paint industry sludges have a higher SiO2 content with 17.2 ± 0.2 % by mass and different phases present in the sludges such as albite, quartz, and rutile were identified, as well as metals of interest in pigments such as iron, chrome, and zinc. Demonstrating that even though the matrix is highly complex, there are routes for the use of this residue.